2013
DOI: 10.1108/01437731311321896
|View full text |Cite
|
Sign up to set email alerts
|

Towards a model of effective group facilitation

Abstract: Purpose -This paper aims to report on research into managers' and facilitators' perceptions of effective facilitation. Design/methodology/approach -A total of 20 managers from across five industry sectors, and 20 facilitators from larger organisations or working as consultants, were interviewed in-depth regarding stories of effective and wholly or partially ineffective facilitation experiences. These stories are analysed within a constructivist-interpretivist paradigm. Findings -Four stages important to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…From this perspective facilitation is then seen as "process in which a person whose selection is acceptable to all member of the group, is substantively neutral, and has no substantive decision-making authority diagnoses and intervenes to help a group improve how it identifies and solves problems and makes decisions, to increase the group's effectiveness" (Schwartz 2005: 21). Facilitators can be internal or external to the organization in which the work group operates, have no decision making authority, and are formally recognized by group members to assist them with the completion of their task (Wardale 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective facilitation is then seen as "process in which a person whose selection is acceptable to all member of the group, is substantively neutral, and has no substantive decision-making authority diagnoses and intervenes to help a group improve how it identifies and solves problems and makes decisions, to increase the group's effectiveness" (Schwartz 2005: 21). Facilitators can be internal or external to the organization in which the work group operates, have no decision making authority, and are formally recognized by group members to assist them with the completion of their task (Wardale 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Azadegan and Kolfschoten 2012;Gregory and Romm 2001;Hunter and Thorpe 2005;Kaner 2007;Lieberman Baker and Fraser 2005;Schein 1999), or intervention design (e.g. Kolfschoten et al 2007;McFadzean and Nelson 1998;Wardale 2013). Although useful, this type of frameworks gloss over the complex interactional processes by which facilitated group work is actually achieved.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is especially the case for government related organizations that face big pressure to localize their workforce. These two limitations were mitigated to some extent by increasing the reliability of the data through selective sampling of respondents that (1) have in-depth knowledge of the topics studied, and (2) for maximum variation across different industrial segments and ownership structures [80]. Finally, we only focused on the organizational perspective of OS.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the Coaching AOE clearly has a different focus (Joo, 2005), the literature indicates some overlap between the two areas that may account for their presence in the same cluster according to our analysis. Content expertise is valued highly in both AOEs (Joo, 2005;Wardale, 2013), as is the ability to resolve conflict (Joo, 2005;Kolb & Rothwell, 2002) and skill in providing feedback (Joo, 2005;Kolb & Rothwell, 2002). In Joo (2005), Kolb and Rothwell (2002) and Wardale (2013), it emerges that for the practitioner (whether 'coach' or 'facilitator'), the commitment of the learner/coachee was perceived as central to the success of the process.…”
Section: Learning Facilitationmentioning
confidence: 99%
“…Content expertise is valued highly in both AOEs (Joo, 2005;Wardale, 2013), as is the ability to resolve conflict (Joo, 2005;Kolb & Rothwell, 2002) and skill in providing feedback (Joo, 2005;Kolb & Rothwell, 2002). In Joo (2005), Kolb and Rothwell (2002) and Wardale (2013), it emerges that for the practitioner (whether 'coach' or 'facilitator'), the commitment of the learner/coachee was perceived as central to the success of the process. Wardale (2013) also observed that effective group facilitators were able to switch to the role of 'coaching' and providing 'consulting advice ' (2013, p. 120).…”
Section: Learning Facilitationmentioning
confidence: 99%